2019
DOI: 10.1016/j.geoderma.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Geogenic versus anthropogenic behaviour and geochemical footprint of Al, Na, K and P in the Campania region (Southern Italy) soils through compositional data analysis and enrichment factor

Abstract: Geochemical studies that focus on environmental applications tend to approach the chemical elements as individual entities and may therefore offer only partial and sometimes biased interpretations of their distributions and behaviour. A potential alternative approach is to consider a compositional data analysis, where every element is part of a whole. In this study, an integrated methodology, which included compositional data analysis, multifractal data transformations and interpolation, as well as enrichment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 64 publications
(94 reference statements)
0
12
0
1
Order By: Relevance
“…As previous reported, the enrichment factor (EF) for studied metals [55] has been employed for calculating differences between the metals originating from human activities and those from natural sources and it can also be used to assess and explain the contamination of metals in soils [108]. To access the degree of soil contamination through this factor, the local background values were used as it is easier to isolate anthropogenic factors from the geogenic ones, because when using generalized values, spurious enrichment due to natural local concentrations of elements may appear [109,110,111,112].…”
Section: Resultsmentioning
confidence: 99%
“…As previous reported, the enrichment factor (EF) for studied metals [55] has been employed for calculating differences between the metals originating from human activities and those from natural sources and it can also be used to assess and explain the contamination of metals in soils [108]. To access the degree of soil contamination through this factor, the local background values were used as it is easier to isolate anthropogenic factors from the geogenic ones, because when using generalized values, spurious enrichment due to natural local concentrations of elements may appear [109,110,111,112].…”
Section: Resultsmentioning
confidence: 99%
“…Domestic waste may be one of the main factors that increase phosphate concentrations in the KJT water area. Various studies have shown that human activities, including household waste, have increased the concentration of contaminants in the oceans, such as nitrogen (Jickells et al, 2017), phosphate (Badawy et al, 2018;Thiombane et al, 2019), and heavy metals (Chu et al, 2019;Bessa et al, 2021). It is indicated by the distribution of phosphate levels at stations 1 to 5, which is higher than the other five observation stations.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the anthropogenic impacts, soil contamination assessment was done by calculation of the enrichment factor (EF), which is a widely used proxy (e.g. Akopyan et al, 2018;Barbieri, 2016;Bern et al, 2019;Cevik et al, 2009;Ghrefat et al, 2011;Liénard et al, 2014;Thiombane et al, 2019;Zhang et al, 2014). The deep soil of the NGSLQ program in China shows little effect of human activities.…”
Section: Anthropogenic Impactsmentioning
confidence: 99%